Noninvasive detection of microaneurysms in diabetic retinopathy by swept-source optical coherence tomography - Cheng S (Dove Medical Press, 2016)
Sarah Cheng, Theodore Leng Department of Ophthalmology, Byers Eye Institute at Stanford, Stanford University School of Medicine, Palo Alto, CA, USA Background and objectives: A method of identifying retinal vascular microaneurysms (MAs) in nonproliferative diabetic retinopathy (NPDR) using swept-source optical coherence tomography (SS-OCT). Patients and methods: SS-OCT images were acquired in 17 eyes with NPDR using prototype SS-OCT device and fluorescein angiography (FA) images were obtained simultaneously. MAs identified on SS-OCT slabs were correlated to MAs identified on FA. Results: MAs were identified in SS-OCT slabs in 15/17 eyes, resulting in NPDR diagnosis rate of 88%. Mean number of MAs identified on FA was 11.7±11.9 (total 199) and was 8.1±9.3 (total 137) on SS-OCT. Wilcoxon rank sum test showed no significant difference in MAs detected on SS-OCT and FA (P=0.2995) across eyes. Wilcoxon rank sum test showed SS-OCT detected slightly fewer MAs than FA per eye (3.65 less, P=0.0009). Conclusion: SS-OCT visualization of MAs could serve as a tool for diagnosing NPDR, and possibly applied as an imaging biomarker for population-based diabetic retinopathy screening. Keywords: diabetic retinopathy, swept-source optical coherence tomography, optical coherence tomography